Peran Pemerintah Provinsi Kalimantan Timur Dalam Mengatasi Penambangan Batubara Tanpa Izin : Kalimantan Timur Dalam Mengatasi Penambangan Batubara Tanpa Izin - Riantori Panandito, Muhammad Rizky (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2025)
This study aims to examine the role of the East Kalimantan provincial government in addressing illegal coal mining activities and analyze the supporting and inhibiting factors, as well as its impact on the environment. This study uses an empirical legal approach, with data collection techniques through field studies, observations, and interviews with officials from the Energy and Mineral Resources (ESDM) Agency and affected communities. The results indicate that despite various monitoring and development efforts, the role of the East Kalimantan provincial government in addressing illegal mining remains suboptimal, particularly in terms of legal enforcement and social control. Supporting factors such as regulations and cross-agency coordination are in place, but are hampered by weak law enforcement, limited resources, and low public awareness. This study recommends strengthening synergy between agencies, optimizing integrated supervision, and empowering communities through education and sustainable economic alternatives. These efforts are crucial to preventing broader environmental damage and maintaining the well-being of communities surrounding mining sites.